The Role of human resource management practices on the job satisfaction of employees in Tishreen University, Central Administration: دراسة ميدانية - اسبر لمى; سهى سنكري (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aims to determine the impact of human resource management practices (training and rehabilitation - wages and compensation) and the extent of their application in the central administration at Tishreen University and their impact on the job satisfaction of employees. And to clarify the importance of these practices in enhancing and raising employee satisfaction. The research also aimed to draw attention to the importance of employee satisfaction. work and raise the level of the institution and its performance. In order to achieve the objectives of the research, the researchers developed a questionnaire in order to collect the primary data from the study samples, which are 57 questionnaires. The questionnaires are analyzed using the Statistical Package for Social Sciences (SPSS) using a number of analyzes, and the study concluded several conclusions that the involvement of all employees in the central administration in training courses to use the computer in their work was at the required level. There is also a weakness in the productivity of the central administration’s database with regard to the current skills of employees, and employee training activities. The research concluded with a number of recommendations, the most important of which are: working to involve all employees in training courses for the use of computers in their work. Enhancing the productivity of the central administration database with regard to the current skills of employees, employee training activities, and enhancing the university’s interest in the great importance of the ISO certificate related to employee training.